A beautiful mind - Grazer, Brian; Goldsman, Akiva; Howard, Ron; Dreamworks Pictures; Universal Pictures; Imagine Entertainment (Universal city, CA : DreamWorks, 2001)
Dramatic biography of John Nash, a mathematical genius, who made an astonishing discovery early in his career and stood on the brink of international acclaim. But the handsome and arrogant Nash soon found himself on a painful and harrowing journey of self-discovery. After many years of struggle, he eventually triumphed over his schizophrenia, and finally, late in life, received the Nobel Prize
Title from title screen
Director of photography, Roger Deakins ; art director, Robert Guerra ; editors, Mike Hill, Dan Hanley ; music composer, James Horner ; costume designer, Rita Ryack ; production designer, Wynn Thomas
Cast: Russell Crowe, Ed Harris, Jennifer Connelly, Paul Bettany, Adam Goldberg, Judd Hirsch, Josh Lucas, Anthony Rapp, Christopher Plummer
DVD Format
Keywords: Nash, John F. -- Drama; Mathematicians -- United States -- Drama; Feature films